The Large Action of Chlorpromazine: Translational and Transdisciplinary Considerations in the Face of COVID-19 - Stip, Emmanuel; Rizvi, Tahir A.; Mustafa, Farah; Javaid, Syed; Aburuz, Salahdein; Ahmed, Nahida Nayaz; Abdel Aziz, Karim; Arnone, Danilo; Subbarayan, Aravinthan; Al Mugaddam, Fadwa; Khan, Gulfaraz (Frontiers in Pharmacology, 2020)
Coronavirus disease 2019 (COVID-19) is a severe acute respiratory syndrome (SARS) in humans that is caused by SARS-associated coronavirus type 2 (SARS-CoV-2). In the context of COVID-19, several aspects of the relations between psychiatry and the pandemic due to the coronavirus have been described. Some drugs used as antiviral medication have neuropsychiatric side effects, and conversely some psychotropic drugs have antiviral properties. Chlorpromazine (CPZ, Largactil®) is a well established antipsychotic medication that has recently been proposed to have antiviral activity against SARS-CoV-2. This review aims to 1) inform health care professionals and scientists about the history of CPZ use in psychiatry and its potential anti-SARS-CoV-2 activities 2) inform psychiatrists about its potential anti-SARS-CoV-2 activities, and 3) propose a research protocol for investigating the use of CPZ in the treatment of COVID-19 during the potential second wave.The history of CPZ's discovery and development is described in addition to the review of literature from published studies within the discipline of virology related to CPZ. The early stages of infection with coronavirus are critical events in the course of the viral cycle. In particular, viral entry is the first step in the interaction between the virus and the cell that can initiate, maintain, and spread the infection. The possible mechanism of action of CPZ is related to virus cell entry via clathrin-mediated endocytosis. Therefore, CPZ could be useful to treat COVID-19 patients provided that its efficacy is evaluated in adequate and well conducted clinical trials. Interestingly, clinical trials of very good quality are in progress. However more 3 information is still needed about the appropriate dosage regimen. In short, CPZ repositioning is defined as a new use beyond the field of psychiatry.